Effect of Dexmedetomidine-Assisted Intravenous Inhalation Combined Anesthesia on Cerebral Oxygen Metabolism and Serum Th1/Th2 Level in Elderly Colorectal Cancer Patients - Tang, Yixun; Liu, Jitong; Huang, Xiaoling; Ding, Huijuan; Tan, Suhong; Zhu, Yimin (Frontiers in Surgery, 2022)
Objective To observe the effect of dexmedetomidine-assisted intravenous inhalation combined anesthesia on cerebral oxygen metabolism and serum Th1/Th2 levels in elderly patients with colorectal cancer. Method 100 elderly patients undergoing elective laparoscopic radical resection of colorectal cancer were prospectively selected and randomly divided into two group. Before induction of anesthesia, the loading dose of dexmedetomidine was given at 0.5 μg/kg, and the infusion time was 15 minutes. After tracheal intubation, 0.4 μg/kg/h dexmedetomidine was continuously pumped, and the infusion was stopped 40 minutes before the end of the operation .In the control group, the same amount of 0.9% sodium chloride was injected intravenously in the same way. 30min before induction of anesthesia (T0), immediately before induction of anesthesia (T1), immediately after tracheal intubation (T2), 40min before operation (T3), and immediately after operation (T4), record the blood oxygen content of the artery and internal jugular vein Difference (D(a-jv)O2), brain oxygen uptake rate (COER%), brain oxygen saturation (rSO2) mean. VAS scale, Ramsay scale, MoCA scale were taken at 6h, 12h, 24h, and 48h postoperatively to evaluate analgesia, sedation, and cognitive function. And monitor the levels of IFN-γ, IL-4, MBP, NSE and S100β. The occurrence of restlessness and adverse reactions during the recovery period of the two groups were compared. Result The levels of D(a-jv)O2, COER%, and rSO2 in two group were higher than the preoperative basic values at T2, T3, and T4 (P<0.05); The levels of D(a-jv)O2, COER%, and rSO2 in the observation group were lower than the control group at T2, T3, and T4 (P<0.05). The VAS score and Ramsay score of the observation group were lower, while the MoCA score was higher than the control group at 6h, 12h, 24h, and 48h after surgery (P<0.05). In addition, the serum IFN-γ, MBP, NSE and S100β levels of the observation group were lower, and the ratio of IFN-γ/IL-4 was higher than the control group (P<0.05). Conclusion Dexmedetomidine-assisted combined intravenous and inhalation anesthesia is beneficial to reduce perioperative cerebral oxygen metabolism and improve postoperative immunosuppression in elderly patients with colorectal cancer. It has a certain protective effect on nerve injury after operation.